Religious attendance, depressive symptoms, and sleep disturbance in older Mexican Americans - Hill, Terrence D. (Mental health, religion & culture, 2020)
Although numerous studies have shown that religious involvement is associated with better health across the life course, researchers have virtually ignored possible links between religious involvement and sleep-related outcomes. Building on previous work, we tested whether religious attendance is inversely associated with sleep disturbance among older Mexican Americans. We also assessed whether depressive symptoms mediate the association between religious attendance and sleep disturbance. Our mediation model was tested using ordinary least squares regression and conditional process analysis of cross-sectional data from the original cohort of the Hispanic Established Population for the Epidemiologic Study of the Elderly. Regression models show that religious attendance is inversely associated with depressive symptoms and sleep disturbance. Mediation analyses indicate that depressive symptoms mediate the association between religious attendance and sleep disturbance. These findings contribute to previous work by showing that religious attendance may protect against sleep disturbance by promoting mental health among older Mexican Americans.